Severe Acute Respiratory Syndrome Coronavirus 2 Infection Symptoms in Pregnancy and Maternal and Neonatal Complications Due to COVID-19: A Systematic Review - Sepideh Miraj; Azadeh Asgarian; Abolfazl Mohammadbeigi; Maryam Derakhshani (Journal of Human Reproductive Sciences)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in pregnant women is associated with severe maternal and neonatal complications including maternal and newborn death. Aims: This review aimed to assess the SARS-CoV-2 infection symptoms during pregnancy as well as maternal and neonatal complications in Iran. Settings and Design: A developing and low-income country and a systematic review. Materials and Methods: International scientific databases including PubMed, Web of Science, Scopus and Google Scholar were searched in a systematic review manner. Two independent researchers were checked and identified articles from September 2019 to September 2022 based on eligibility criteria and quality appraisal. The results of review were reported in two sections including maternal and neonatal outcomes. Statistical Analysis Used: Descriptive statistics was used for statistical analysis. Results: Seventeen studies including 870 pregnant mothers with COVID-19 met the eligibility criteria and were reviewed. The main maternal consequences of COVID-19 were intensive care unit (ICU) admission, pre-term delivery, maternal death, pre-mature rupture of membranes, pre-eclampsia, intrauterine growth retardation and stillbirth. Neonatal ICU admission, newborn death, neonatal sepsis, low birth weight and respiratory distress syndrome, tachypnoea, asphyxia and pneumothorax were the most common outcomes of COVID-19 infection in offspring of pregnant subjects. Conclusion: Pregnant mothers with COVID-19 infection are at higher risk of being admitted to the ICU and mechanical ventilation and consequently maternal and neonatal death. Comparing the maternal and foetal consequences in different ethnicities, regions and countries may be related to the socioeconomic status of people and should be considered with respect to different determines. Moreover, the maternal and neonatal complications due to COVID-19 infection in Iran and other developing countries seem to be higher than other countries.